From Allies to Enemies: The Dynamics of the Relationship Between the Sultanate of Palembang and Britain, 1810-1812 - Wisnu Febriano; Uswatun Hasanah; Agus Mahfudin Setiawan (Universitas Islam Negeri Sumatera Utara, 2026)
This article examines the dynamics between the Palembang Sultanate and the British from 1810 to 1812. Initially a strategic alliance, the relationship deteriorated into a confrontation due to conflicts of colonial interest in monopolizing the region's main commodities. This research employs a systematic historical method, encompassing heuristics, source criticism, interpretation, and historiography to analyze conflicting interests as the primary factor behind the relationship's breakdown. Primary sources include Raffles' letters, colonial archives, and memoirs, which are combined with secondary sources. The findings indicate that Raffles' letters successfully influenced Sultan Mahmud Badaruddin II to ally against the Franco-Dutch forces, culminating in a mass massacre in September 1811. Subsequently, Raffles exploited this situation to seize the tin-rich Bangka Island after the Sultan refused to hand it over. This refusal triggered Raffles' attack on Palembang. As the British fleet entered the Musi River and occupied Borang Island Fort, Sultan Mahmud Badaruddin II and his family fled. Raffles then appointed Raden Husin Dhiauddin as Ahmad Nadjamuddin II, establishing him as a British puppet. This conflict reflects colonial exploitation that remains relevant to this day.